ANALISA KANDUNGAN POLIAROMATIK HIDROCARBON PADA GAS BUANG KENDARAAN BERMOTOR BERBAHAN BAKAR DIESEL, AIR LAUT DAN SEDIMEN YANG TERKONTAMINASI TUMPAHAN MINYAK - Zulaihah, Lilik (Bina Teknika, 2015)
PAH tend to bind with organic and inorganic material suspended so abundant in bottom sediments. PAHs enter the water through various sources are quickly absorbed by organic and inorganic particles. PAH accumulated by aquatic biota higher than womb environment. This study aims to determine the type and content of polyaromatic hydrocarbons both in the exhaust emissions of motor vehicles as well as diesel fuel in sea water and sediments contaminated by the oil spill. The results showed that Chrysene, benzo (b) Fluoranthene and Benzo (a) Pyrene is a sample that had higher levels of PAH is quite high and is found in every sample well on exhaust emissions as well as in seawater and sediments, where all three types of PAH that exceed the threshold determined doubled. While the content of PAHs found in terminal loading and unloading of ships Benzo (b) fluoren namely 92.842 ppm and below Benzo (a) pyren 62.054 ppm and 10.939 Chrysene pp.